Economic Strain, Ethnic Concentration and Attitudes Towards Foreigners in the European Union - Ira N. Gang; Francisco L. Rivera-Batiz; Myeong-Su Yun (Institute for the Study of Labor (IZA), 2002)
This paper provides a statistical analysis of the determinants of attitudes towards foreigners displayed by Europeans sampled in Eurobarometer surveys in 1988 and 1997. Europeans who compete with immigrants in the labor market have more negative attitudes towards foreigners. In addition, an increased concentration of immigrants in local neighborhoods increases the likelihood of negative attitudes. Racial prejudice exerts a strong influence on anti-foreigner sentiment. The generally rising trend towards greater racial prejudice, and the decline in the strength of educational attainment in reducing negative attitudes towards foreigners, contribute to the increasing anti-foreigner attitudes between 1988 and 1997.
Keywords: F22; J61; J15; 330; anti-foreigner; labor force status; ethnic concentration; probit decomposition; racial prejudice; attitudes; sentiments towards migrants; Ethnische Diskriminierung; Erwerbsstatus; Migranten; Arbeitsmarkt; EU-Staaten